Sāvitrī and Resurrection: The Ideal of devoted wife, her forehead mark, Satī, and human sacrifice in Epic-Purāṇic, Vedic, Harappan-Dravidian and Near Eastern perspectives - Parpola, Asko (Studia Orientalia Electronica, 2014)
No abstract